Senior Citizens Protesting at Exhibit Hall Mayor Dan Whitehurst Funding Policies - Watkins, Howard::::::::: (1981)
Bob Lincon holding sign "WHITEHURST Betrays Renters and Seniors!!" followed by several elderly women carrying signs